On the Maintenance of Large-Scale Elixir Tests - Barbosa, Livia Almeida (Anais do Workshop em Engenharia de Software para Programação Funcional (SE4FP), 2025)
This paper discusses how a global company maintains its test suite, which currently has over 95,000 test cases. While growing its products using an Elixir monolithic codebase, the team developed and evolved guidelines and patterns for writing tests and managing unreliable (flaky) tests while keeping the developer experience and the CI/CD time up to standards.